The Impact of Board Gender Diversity on Firms' M&A Activity : Evidence from Nordic Listed Companies - Hellberg, Kasper (My University, 2025)
This thesis investigates the impact of board gender diversity on M&A activity of the Nordic listed firms in Denmark, Finland, Norway and Sweden between 2010 and 2022. Moreover, the purpose of this thesis is to investigate in more detail the association between board gender diversity, number of M&A transactions (acquisitiveness) and the deal size (transaction price) in euros. The prior academic literature has documented behavioral differences between genders in terms of their behavior under risk. Given that M&As are considered strategic activities that carry risk, the differences between genders can impact on the overall M&A outcome in both terms of the number of transactions, as well as the size of the transaction. Despite the increased amount of attention, female representation among corporate boards is still relatively low globally. The change towards more diverse boards has already started within the firms in the EU, as the new regulation requires corporate boards to give at least 40% of seats in corporate boards to the underrepresented gender by June 2026. Nordic countries are considered as pioneers regarding gender diversity. In 2023 41% of board directors in the Nordics were women, and 47% of all new directors were women, which already exceeds the 40% requirement set by the European Union. The main methodology to test the association between firms9 board gender diversity and M&A activity for both hypotheses is Ordinary Least Square (OLS) regression. The regressions are run separately for each country to be able compare the results between the countries. In addition, all transaction prices are also converted to euros to make the results for the second hypothesis comparable as well. Results of this thesis are twobranched. Findings for the first hypothesis suggest that there is a negative relationship between board gender diversity and firms' M&A activity as measured by the number of M&A transactions. The results are statistically significant for all four Nordic countries, indicating that firms with more diverse boards tend to make less M&A transactions on average. Empirical findings for the second hypothesis suggest that there is a negative association between board gender diversity and M&A transaction price in all four countries. However, the results are statistically significant only in Finland, Norway and Sweden, indicating that firms with more women in boards tend to execute smaller M&A deals on average. Going forward, the EU's new requirement regarding the proportion of underrepresented gender in corporate boards will open new research opportunities focusing on how the enhanced position of female board members impacts for example, to board competence, board selection process or the impact of increased board gender diversity on different corporate outcomes. It is also interesting to see if the new legislation will eventually result in increased number of individual female board members, or will certain individual females act as board members for several corporations.

Tämä tutkielma tarkastelee hallitusten sukupuolijakauman vaikutusta pohjoismaisten pörssiyhtiöiden yrityskauppatoimintaan Tanskassa, Suomessa, Norjassa ja Ruotsissa vuosina 2010–2022. Lisäksi tutkielman tarkoituksena on analysoida tarkemmin hallitusten sukupuolten monimuotoisuuden, yritysostojen lukumäärän (yritysostointensiivisyyden) ja kauppahinnan (kauppahinta euroina) välistä yhteyttä. Aiempi akateeminen kirjallisuus on dokumentoinut sukupuolten välisiä eroja käyttäytymisessä erityisesti riskinottoon liittyen. Koska yritysostot ovat strategisia päätöksiä, joihin liittyy merkittäviä riskejä, sukupuolten väliset erot voivat vaikuttaa yritysostojen lopputulokseen sekä transaktioiden lukumäärän että niiden koon osalta. Kasvaneesta mediahuomiosta huolimatta, naisten edustus yritysten hallituksissa on edelleen suhteellisen vähäistä maailmanlaajuisesti. Euroopan unionin yrityksissä muutos kohti monimuotoisempia hallituksia on kuitenkin jo alkanut, sillä uusi sääntely edellyttää, että vähintään 40 % hallituspaikoista on annettava aliedustetulle sukupuolelle kesäkuuhun 2026 mennessä. Pohjoismaita pidetään sukupuolten monimuotoisuuden edelläkävijöinä. Vuonna 2023 hallitusten jäsenistä 41 % oli naisia, ja uusista hallitusjäsenistä naisten osuus oli 47 %, mikä ylittää jo valmiiksi Euroopan unionin asettaman 40 prosentin vaatimuksen. Tämän tutkielman molempia hypoteeseja testataan pienimmän neliösumman menetelmään (OLS) regressioanalyysillä. Hypoteeseja testataan erikseen kullekin maalle, jotta tuloksia voidaan vertailla maiden välillä. Lisäksi kaikki kauppahinnat on muunnettu euroiksi, jotta myös toisen hypoteesin tulokset ovat keskenään vertailukelpoisia. Tutkielman tulokset ovat kaksijakoisia. Ensimmäisen hypoteesin osalta havainnot viittaavat siihen, että hallitusten sukupuolten monimuotoisuuden ja yritysostotoiminnan välillä on negatiivinen yhteys, kun yritysostointensiivisyyttä mitataan yritysostojen lukumäärällä. Tulokset ovat tilastollisesti merkitseviä kaikissa neljässä Pohjoismaassa, mikä viittaa siihen, että monimuotoisemmat hallitukset tekevät keskimäärin vähemmän yritysostoja. Toisen hypoteesin osalta empiiriset havainnot viittaavat siihen, että hallitusten sukupuolten monimuotoisuuden ja yrityskauppojen kauppahinnan välillä on negatiivinen yhteys kaikissa neljässä maassa. Tulokset ovat kuitenkin tilastollisesti merkitseviä vain Suomessa, Norjassa ja Ruotsissa, mikä tarkoittaa, että yritykset, joiden hallituksissa on enemmän naisia, tekevät keskimäärin pienempiä yritysostoja. Jatkossa EU:n uusi vaatimus aliedustetun sukupuolen osuudesta yritysten hallituksissa avaa uusia tutkimusmahdollisuuksia. Tulevissa tutkimuksissa voidaan tarkastella esimerkiksi sitä, miten naisten vahvistunut asema hallituksissa vaikuttaa hallituksen osaamiseen, valintaprosessiin tai sukupuolten monimuotoisuuden lisääntymisen vaikutuksiin eri yritystuloksissa. On myös mielenkiintoista seurata, johtaako uusi lainsäädäntö lopulta naishallitusten jäsenten määrän kasvuun vai tuleeko tietyistä naisjohtajista useiden yritysten hallituksen jäseniä.
Keywords: diversity; quotas; mergers; acquisition; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance